Health education needs in chronic kidney disease patients with continuous ambulatory peritoneal dialysis therapy at Dr. Saiful Anwar Hospital, Malang: a qualitative study - Tsaqiba, Tsania Nurjihan; Padmawati, Retna Siwi; Ratrikaningtyas, Prima Dhewi (Universitas Gadjah Mada, 2024)
Purpose: This study aims to describe the need for health education programs for Chronic Kidney Disease (CKD) patients undergoing Continuous Ambulatory Peritoneal Dialysis (CAPD) therapy at Dr. Saiful Anwar Hospital, Malang. Methods: This research employs a qualitative case study approach. Data collection was conducted through in-depth interviews and observations of 18 informants. Results: Patients with chronic kidney disease (CKD) undergoing continuous ambulatory peritoneal dialysis (CAPD) at Dr. Saiful Anwar Hospital in Malang have shared various experiences related to their treatment. For instance, these patients have expressed concerns about being advised against pregnancy. A notable advantage of CAPD therapy is that it allows for fewer dietary restrictions, enabling patients to consume a broader range of foods. However, many CAPD patients also experience feelings of sadness and depression related to their condition. To address these challenges, patients in CAPD therapy require regular health education. Education can be provided through both online and offline methods, with sessions planned every one to six months. Health education content: CKD patients undergoing CAPD therapy require additional content tailored to their specific needs, considering the duration of CAPD use. Novice patients need health education about psychological conditions. Meanwhile, intermediate patients need content about new types of CKD therapy, psychological treatment, vitamins and drugs, and lifestyle for CAPD patients. Long-time patients require content on mental and physical activity, as well as guidance on maintaining healthy bones and skin. Conclusion: CKD patients with CAPD therapy have a positive perception and require additional health education activities regularly. Health education content can be customized to suit the patient's condition and the duration of Continuous Ambulatory Peritoneal Dialysis (CAPD). The delivery of health education for Chronic Kidney Disease (CKD) patients undergoing CAPD therapy can be conducted through group sessions, individual consultations, or mass methods, including the use of patient WhatsApp groups.